Altered hypothalamic functional connectivity in cluster headache: a longitudinal resting-state functional MRI study. Issue 4 (30th June 2014) - Yang, Fu-Chi; Chou, Kun-Hsien; Fuh, Jong-Ling; Lee, Pei-Lin; Lirng, Jiing-Feng; Lin, Yung-Yang; Lin, Ching-Po; Wang, Shuu-Jiun
Abstract : Background: Neuroimaging studies implicate hypothalamic dysfunction in the pathogenesis of cluster headache (CH). Disruptions in non-traditional pain processing areas, including the cerebellum and visual cortex, have also been reported in CH. It is unknown whether the hypothalamus interacts significantly with these areas, and whether any such interactions vary between the 'in-bout' and 'out-of-bout' periods in CH. This study aimed to investigate the resting-state functional connectivity (FC) of the hypothalamus of patients with CH. Methods: Using 3-T functional MRI, we conducted a seed-based resting-state intrinsic FC analysis of the hypothalamus in 18 episodic CH patients during in-bout and out-of-bout periods, and in 19 healthy controls. Correlations between hypothalamic FC and clinical variables were also assessed. Results: Compared to controls, CH patients showed hypothalamic FC changes with the medial frontal gyrus and occipital cuneus during in-bout and out-of-bout periods. Compared to out-of-bout scans, in-bout scans revealed decreased hypothalamic FC with the medial frontal gyrus, precuneus, and cerebellar areas (tonsil, declive and culmen). Additionally, the annual bout frequency correlated significantly with the hypothalamic FC in the cerebellar culmen (r=−0.576, p=0.02) and cerebellar declive (r=−0.522, p=0.038). Conclusions: Our findings suggest that in CH, FC differences between the hypothalamus and its regional distribution extends beyond traditional pain processing areas, primarily to the cerebellar, frontal and occipital areas. These changes may be important and associated with CH pathophysiology.